Features of digital marketing - Kolodnik, Tatiana D. (Journal of the Belarusian State University. Economics, 2021)
This author explores the features of digital marketing. The article analyses the impact of digitalisation on the formation of digital marketing channels and tools, transferred as IT infrastructure and network technologies. The article provides a view on the organisation of complex events and discusses trends in the development of digital marketing.
Keywords: digitalisation; digital marketing; IT infrastructure and network technologies; digital marketing channels; digital marketing tools; digital marketing events